The Correlation Between Students’ Self Efficacy, Motivation, And English Learning Outcomes - Zahra Husnul Khatimah; Abdul Syahid; Zaitun Qamariah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
The recent decade has witnessed the worse condition of Indonesian students’ learning loss which commonly caused by lack of self control. In handling that, students need the confidence to enhance their self-control which has been referred in literature as self-efficacy and motivation. The research aims to measure the correlation of self-efficacy and motivation towards students’ English learning outcomes. 34 students in grade 10 at MA Darul Ulum Palangka Raya were polled quantitatively using 24 self-efficacy and motivational questions. Multiple linear regressions was aplied to examine the data. The finding is, both variables are positively correlated with students' English test scores (F=38.025, p=0.000). students’ english result was correlated 67,20% by self-efficacy(x1), and motivation (x2) 3,80%, The total contribution was 71%. Other variables not under examination had an impact on the remaining 29%.